Identification of a highly conserved valine-glycine-phenylalanine amino acid triplet required for HIV-1 Nef function - Meuwissen, Pieter; Stolp-Rastätter, Bettina; Fackler, Oliver Till (Retrovirology, 2012)
Background: The Nef protein of HIV facilitates virus replication and disease progression in infected patients. This role as pathogenesis factor depends on several genetically separable Nef functions that are mediated by interactions of highly conserved protein-protein interaction motifs with different host cell proteins. By studying the functionality of a series of nef alleles from clinical isolates, we identified a dysfunctional HIV group O Nef in which a highly conserved valine-glycine-phenylalanine (VGF) region, which links a preceding acidic cluster with the following proline-rich motif into an amphipathic surface was deleted. In this study, we aimed to study the functional importance of this VGF region. Results: The dysfunctional HIV group O8 nef allele was restored to the consensus sequence, and mutants of canonical (NL4.3, NA-7, SF2) and non-canonical (B2 and C1422) HIV-1 group M nef alleles were generated in which the amino acids of the VGF region were changed into alanines (VGF→AAA) and tested for their capacity to interfere with surface receptor trafficking, signal transduction and enhancement of viral replication and infectivity. We found the VGF motif, and each individual amino acid of this motif, to be critical for downregulation of MHC-I and CXCR4. Moreover, Nef’s association with the cellular p21-activated kinase 2 (PAK2), the resulting deregulation of cofilin and inhibition of host cell actin remodeling, and targeting of Lck kinase to the trans-golgi-network (TGN) were affected as well. Of particular interest, VGF integrity was essential for Nef-mediated enhancement of HIV virion infectivity and HIV replication in peripheral blood lymphocytes. For targeting of Lck kinase to the TGN and viral infectivity, especially the phenylalanine of the triplet was essential. At the molecular level, the VGF motif was required for the physical interaction of the adjacent proline-rich motif with Hck. Conclusion: Based on these findings, we propose that this highly conserved three amino acid VGF motif together with the acidic cluster and the proline-rich motif form a previously unrecognized amphipathic surface on Nef. This surface appears to be essential for the majority of Nef functions and thus represents a prime target for the pharmacological inhibition of Nef.